Synchronized acoustic emission and high-speed imaging of cavitation-induced atomization: The role of shock waves - Abhinav Priyadarshi; Paul Prentice; Dmitry Eskin; Peter D. Lee; Iakovos Tzanakis (Ultrasonics Sonochemistry)
This study experimentally investigates the role of cavitation-induced shock waves in initiating and destabilizing capillary (surface) waves on a droplet surface, preceding atomization. Acoustic emissions and interfacial wave dynamics were simultaneously monitored in droplets of different liquids (water, isopropyl alcohol and glycerol), using a calibrated fiber-optic hydrophone and high-speed imaging. Spectral analysis of the hydrophone data revealed distinct subharmonic frequency peaks in the acoustic spectrum correlated with the wavelength of capillary waves, which were optically captured during the onset of atomization from the repetitive imploding bubbles. This finding provides the first direct evidence that the wavelength of the growing surface waves, which governs capillary instability resulting in droplet breakup, is linked to the periodicity of shock waves responsible for the onset of the subharmonic frequencies detected in the acoustic spectra. This work contributes to a deeper understanding of ultrasonic atomization, signifying the role of cavitation and shock waves in the atomization process.